Seasonal Variations in the Chemical Parameters of Salt in Various Salt-pans of Kanyakumari District - Vaithyanathan, C.; Umayoru Bhagan, V. (Asian Journal of Chemistry, 2010)
The seasonal variations in the chemical parameters of the salt samples collected from various salt-pans of Kanyakumari district were studied. Parameters like the percentage of moisture, insoluble impurities, calcium sulphate, magnesium sulphate, magnesium chloride and sodium chloride were analyzed. Variations in the different samples were observed and it was due to the atmospheric climate and strong dusty winds.